2016
DOI: 10.1037/dev0000174
|View full text |Cite
|
Sign up to set email alerts
|

Experience facilitates the emergence of sharing behavior among 7.5-month-old infants.

Abstract: Given the centrality of prosociality in everyday social functioning, understanding the factors and mechanisms underlying the origins of prosocial development is of critical importance. This experiment investigated whether experience with reciprocal object exchanges can drive the developmental onset of sharing behavior. Seven-month-old infants took part in two laboratory visits to assess their sharing behavior and ability to release objects. During the intervening 7 −14 day period parents led infants in an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…Previous research has demonstrated that other aspects of infants’ fairness understanding is shaped by early experiences. For instance, the presence of siblings is related to infants’ fairness expectations [ 35 ], and both parental empathy and previous experience sharing is correlated with early prosocial behaviors [ 41 ]. Future research should test the extent to which these variables also influence infants’ ability to use fairness information when selecting a social partner.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that other aspects of infants’ fairness understanding is shaped by early experiences. For instance, the presence of siblings is related to infants’ fairness expectations [ 35 ], and both parental empathy and previous experience sharing is correlated with early prosocial behaviors [ 41 ]. Future research should test the extent to which these variables also influence infants’ ability to use fairness information when selecting a social partner.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, parents of 18‐month‐old nonhelpers on the instrumental task reported that they were less engaged in socializing their toddlers' prosocial behavior than were the parents of helpers. Other recent research has reported relations between parents' interactional style and infants' ability to encode goal‐directed actions (Licata et al., ); between parental empathy (Xu, Saether, & Sommerville, ) or perspective taking (Cowell & Decety, ) and sharing in infants and toddlers; between parents' emotion talk with their toddlers and children's helping and sharing (Brownell, Svetlova et al., ); and between parent scaffolding during cleanup and toddlers' helping (Hammond & Carpendale, ; Pettygrove et al., ), in line with the argument that socialization influences multiple aspects of early prosociality and does so in a multitude of ways (Brownell & Early Social Development Research Lab, ). In the current study we cannot determine how parent socialization of prosocial behavior may have influenced toddlers' helping and nonhelping behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These experiences may help infants appreciate the consequences of inequality, and thus account for their tendency to allocate enhanced attention to unfair outcomes. A critical test of this hypothesis would be to conduct sharing interventions with pre-sharing infants, which have been shown to lead to the onset of sharing [29], to see whether they also impact infants’ ability to both detect violations to fairness norms, and assign valence to the actors that perform them.…”
Section: Relations Between Fairness and Sharing: Why Are Fairness Conmentioning
confidence: 99%